Factors influencing cataract awareness and treatment attitudes among the middle-aged and older in western China's rural areas - Guan, Hongyu; Xue, Jing; Ding, Yuxiu; Zhang, Yunyun; Du, Kang; Yang, Jie (Frontiers in Public Health, 2023)
Abstract Purpose: This study was conducted to determine the level of knowledge about cataracts and the associated factors among adults aged 50 and above in rural areas of Qingcheng county in Gansu Province of Western China, 2020. Methods: A large community-based cross-sectional study was conducted among the randomly selected 1503 adults aged 50 and above from October to December 2020. Data were collected by conducting eye examinations and face-to-face interviews. Multivariate binary logistic regression and multivariate linear regression were used to identify associated factors of knowledge about cataracts. Odds Ratio (OR), Coefficient(C), and 95% Confidence Interval (CI) were reported to declare the statistical associations between knowledge about cataracts and the independent variables. Results: Of the 1503 study participants, 1078 (71.7%) had good knowledge about cataracts. The primary school completed [OR = 1.43 (95% CI 1.08–1.90), P=0.012], Secondary school & above [OR = 2.69 (95% CI 1.86–3.89), P<0.001], Examine for cataract [OR = 1.82 (95%CI 1.27–2.62), P=0.001] were positively significantly associated with knowledge about cataracts. Whereas eye examinations [OR = 0.73(95% CI 0.55-0.96), P=0.022] were negatively associated with knowledge about cataracts. Multivariate linear regression analyses showed a significant negative correlation between age and knowledge of cataract treatment options. Living with at least one child was positively correlated with knowledge of the therapeutic effects of cataracts. And monthly household income was significantly positively correlated with knowledge of the therapeutic effects of cataracts, treatment options, and the surgical reimbursement ratio for cataracts. Conclusions: More than one-third of the participants still had poor knowledge about cataracts. The respondents with at least primary education and above, with previous examinations, and with examination for cataracts had significant associations with good knowledge about cataracts. So, it is recommended that stakeholders in different hierarchies organize health education by considering the education level of the community, focusing on cataract treatment knowledge and the surgical reimbursement ratio to improve cataract surgery rates. Keywords: cataract, cataract knowledge, associated factors, rural China, Qingcheng County